Development of Physics Learning Materials STEM-Local Wisdom Oriented to Improving Students' Critical Thinking Skills - Nugraheni Ayu Agustina; Raden Wakhid Akhdinirwanto; Siska Desy Fatmaryanti (Universitas Muhammadiyah Purworejo, 2022)
Research on the implementation of STEM-oriented physics learning and local wisdom has been carried out to determine the feasibility of STEM-oriented physics learning and local wisdom to improve students' critical thinking skills. This study uses the 4D development method, namely Define, Design, Develop, and Disseminate. The subjects of this study were students of class X MIPA at SMA Negeri 6 Purworejo for the academic year 2020/2021. The research data were obtained using interview methods, product validation, critical thinking skills validation, learning implementation validation, and student response questionnaires. The results of this study were obtained: (1) the validity of learning in terms of two expert validators got an average final score of 3.46 and 3.45 from material experts and media experts, so it can be said to be very valid and can be used in limited and broad tests. , (2) the results of the implementation of learning seen from the implementation sheet of learning are stated to be practical, and (3) the improvement of students' critical thinking skills seen from the pretest and posttest scores is always significantly increased and the N-gain is included in the medium category, and (4) getting participant responses positive students with good categories. Thus, it can be concluded that STEM-oriented physics learning and local wisdom are appropriate to be used to improve students' critical thinking skills.